2022
DOI: 10.1021/acsami.2c02977
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Organic Field-Effect Transistors by a Molecular Dopant with High Electron Affinity

Abstract: Organic field-effect transistors (OFETs) are attractive for next-generation electronics, while doping plays an important role in their performance optimization. In this work, a soluble molecular dopant with high electron affinity, CN6-CP, is investigated to manipulate the performance of OFETs with a p-type organic semiconductor as the transport layer. The performance of the model 2,7-didodecyl[1]benzothieno[3,2-b][1]benzothiophene (C12-BTBT) bottom-gate top-contact (BGTC) OFETs is greatly optimized upon doping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Yuanwei Zhu et al doped C12-BTBT with CN6-CP and F4-TCNQ in a BGTC device, respectively. 83 In this work, CN6-CP had higher solubility and showed a higher doping efficiency compared with F4-TCNQ as the dopant under the same conditions. Guanghao Lu reported reactive oxygen (oxygen plasma or ozone) treatments of 2,7didodecyl [1]benzothieno[3,2-b][1]benzothiophene (C12-BTBT), 84 and found that low-pressure oxygen plasma resulted in lowconcentration doping and maintained the hole mobility above 5 cm 2 V À1 s À1 .…”
Section: Channel Dopingmentioning
confidence: 66%
“…Yuanwei Zhu et al doped C12-BTBT with CN6-CP and F4-TCNQ in a BGTC device, respectively. 83 In this work, CN6-CP had higher solubility and showed a higher doping efficiency compared with F4-TCNQ as the dopant under the same conditions. Guanghao Lu reported reactive oxygen (oxygen plasma or ozone) treatments of 2,7didodecyl [1]benzothieno[3,2-b][1]benzothiophene (C12-BTBT), 84 and found that low-pressure oxygen plasma resulted in lowconcentration doping and maintained the hole mobility above 5 cm 2 V À1 s À1 .…”
Section: Channel Dopingmentioning
confidence: 66%
“…To evaluate the R c of the devices, the widely used transmission line method (TLM) is employed, with channel lengths ( L ) ranging from 30 to 200 μm. TLM assumes that the total device resistance ( R on ) is the sum of source/drain R c and the channel resistance ( R ch ) which is proportional to the channel length.…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum doping, on the other hand, enables solvent-free doping and the deposition of a few nanometer-thick dopant molecules on the surface of the conjugated-polymer film, which not only lead to a significant enhancement of the conductivity of the conjugated polymer, but also does not affect the crystallinity of the conjugated-polymer film excessively, ensuring the quality of the conductive film. In addition, vacuum doping is also advantageous in flexible electronic devices, which not only excludes the influence of solvent on the polymer, but also allows precise control of the doping region as well as the doping density in OFETs. …”
Section: Introductionmentioning
confidence: 99%